Effects of estradiol cypionate dose as an ovulatory stimulus on reproductive performance of lactating dairy cows during the summer season - Pereira, M. H.C. [UNESP]; Cappellozza, B. I.; Costa, W. M. [UNESP]; Barbosa, L. [UNESP]; Cerri, R. L.A.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2022)
This experiment was designed to evaluate the effects of increasing doses of estradiol cypionate (ECP) on reproductive function of lactating dairy cows during the summer. In Exp. 1, 643 lactating Holstein cows were blocked by parity and assigned to receive 1) an intravaginal P4 device (1.9 g of P4) and 2.0 mg of estradiol benzoate on day −11, 25 mg (i.m.) of dinoprost tromethamine on day −4, 1.0 mg (i.m.) of estradiol cypionate and CIDR withdrawal on day −2, followed by TAI on day 0 (n = 326; ECP-1) or 2) the same synchronization protocol with 2.0 mg of ECP on day −2 (n = 317; ECP-2). In both treatments, cows were TAI on day 0 of the protocol, and cow rectal temperature was measured on days −2, 0, and 7. In Exp. 2, 608 lactating crossbred Holstein × Gir dairy cows were blocked by parity and enrolled to the same treatments as in Exp. 1, but on day 7, cows received one viable embryo into the uterine horn. In Exp. 1, a greater percentage of ECP-2 cows were detected on estrus (81.3 vs. 91.1%, respectively). A treatment × body condition score (BCS) interaction was observed on day 60 pregnancy per AI (P/AI), as ECP-2 cows with a BCS <2.75 had a greater P/AI vs. ECP-1, but an opposite result was observed in cows with a BCS ≥2.75. Regardless of treatment, there were effects of mean rectal temperature and heat stress events on P/AI. Treatment affected the diameter of the ovulatory follicle at TAI (ECP-1 = 15.3 mm vs. ECP-2 = 14.8 mm) and a greater percentage of ECP-1 cows had larger follicles (≥16.5 mm), but ECP-2 resulted in a greater incidence of early ovulatory cows (ovulating before day 0). Therefore, follicle diameter at TAI affected P/AI on day 60 in cows receiving ECP-2 and tended to affect ECP-1 cows. A treatment effect was observed on time to estrus following ECP treatments and a reduced proportion of ECP-2 cows showed estrus at TAI. Regardless of treatment, cows detected on estrus 48 h after ECP administration had a greater P/AI on day 60 vs. cows detected on estrus 24 h. In Exp. 2, a greater percentage of ECP-2 cows were detected on estrus (68.3 vs. 81.4%, respectively). In summary, a greater dose of ECP increased the percentage of animals expressing estrus, but it did not benefit the reproductive function of lactating dairy cows during the summer, regardless if animals were assigned to a TAI or timed-embryo transfer (TET) protocol.
Keywords: Dairy cows; Embryo transfer; Estradiol cypionate; Hyperthermia; Timed AI